Democracy bytes : new media, new politics and generational change - Bessant, Judith; SpringerLink (Online service). (London : Palgrave Macmillan UK : Palgrave Macmillan, 2014)
This study is about new media, the crisis of democracy and political renewal. It asks: What is the political? How can we understand politics in a network age? Can we talk sensibly about generational change? Analysing four international case studies, this book gives an optimistic assessment of how digital media supports new forms of politics.
Keywords: Science; Science, general